Der Übergang vom Bildungs- in das Beschäftigungssystem in Japan - Teicher, Kerstin [Verfasser]; Teichler, Ulrich [Verfasser] (My University, 1997)
The process of transition from education to employment in Japan is characterized by a relatively early and short period of search and recruitment, whereby the educational institutions play a significant role. A "closed " process of recruitment dominates for secondary school leavers who receive as a rule a single recommendation for a single employer and are likely to be employed on that basis. An "open " process is common for university graduates in humanities and social sciences, whereas graduates from other sectors of higher education experience a mixed system whereby recommendations might help but are not exclusive channels. Since the early 1990s, the transition process underwent changes in the context of increasing mobility and uncertainty of employment as well as a growing appreciation of specific skill and of clear ties between the substance of knowledge and work. (DIPF/Orig.)
Keywords: S 1 Stufen der Berufsbildung; S 1.1 Allgemeinbildende Schule; G 1.2 Arbeitsmarkt; P 2.1.5 Fachhochschul- und Hochschulreife; L Lehren & Lernen; L 5 Beratung & Orientierung; G 2.3 Wandel von Arbeit & Wirtschaft; G 1.3.2 Bildungsverhalten und -verläufe; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; T 3.4 Befragung; I 2.3.4 Asien; Berufsverlauf; Bildungssystem; Schule; Schulleben; Beschäftigungssystem; Prüfung; Hochschule; Lernen; Sozialisation; Absolvent; Berufsanforderung; Übergang; Berufsorientierung; Bewerbung; Wirtschaft; Arbeitsmarkt; Personalpolitik; Berufliche Weiterbildung; Lebenslanges Lernen; Wertewandel; Empirische Untersuchung; Befragung; Vergleich; Quantitative Angaben; Handel; Japan